Commerce and Colonization in the Ancient Near East - Aubet, Maria Eugenia (Cambridge University Press, 2013)
In this analysis of the first colonialisms in history, the eastern roots of the Phoenician colonial system in the first millennium BC are traced and the metropolis of Tyre is established as the final link in a long chain of colonial experiences in the ancient Near East. The author reviews some of the theories and debates about trade and the colonial phenomenon, scrutinises the colonial situations that arose in the East in a context of long-distance interregional trade, and analyses the examples - Egypt, Byblos, Uruk, and Assur - where a metropolis with a mercantile tradition intervenes and acts as intermediary in different interregional exchange circuits. The success of a colonial metropolis is measured by its capacity to integrate dependent and complementary economies in circumstances where there is a strong demand for raw materials by the great powers. In that context, the profits obtained in the colonies thanks to price differentials between one region and another bring us back to the unending debate about the place of the economy in the ancient world and the pertinence of using features from modern economy - such as market, capital, private initiative, laws of supply and demand, and money - to explain the economies of the past.
Humanities
Keywords: archaeology; business & economics; economic history; history / ancient / general